Cavernosum smooth muscle relaxation induced by Schisandrol A via the NO-cGMP signaling pathway - Liu, W; Choi, B R; Bak, Y O; Zhang, L T; Zhou, L X; Huang, Y R; Zhao, C; Park, J K (Cellular and Molecular Biology, 2016)
To evaluate the effect of Schisandrol A on rabbit corpus cavernosum smooth muscle and elucidate the potential mechanism. Penises were obtained from healthy male New Zealand White rabbits (2.5-3.0 kg). The pre-contracted penis with phenylephrine (Phe, 10 µM) was treated with accumulative concentrations of Schisandrol A (10-7, 10-6, 10-5 and 10-4 M). The change in intracavernosum pressure (ICP) and tension was recorded, cyclic nucleotides in the cavernosum tissue were measured by radioimmunoassay, mRNA level and expression of endothelial nitric oxide synthase (eNOS) and neuronal NOS (nNOS) were measured by real time PCR and western blot respectively. The corpus cavernosum smooth muscle relaxation induced by Schisandrol A was in a dose-dependent manner. Pre-treatment with NOS inhibitor (NÏ‰ nitro-L-arginine-methyl ester, L-NAME) or guanylyl cyclase inhibitor (1H-(1,2,4)oxadiazolo(4,3-a)quinoxalin-1-one, ODQ) significantly diminished the relaxation. The cyclic guanosine monophosphate (cGMP) level was significantly increased in the cavernosum tissue. Real time PCR and western blot showed the mRNA level and expression of eNOS and nNOS was also upregulated. Schisandrol A relaxes the cavernosum smooth muscle by activating NO-cGMP signaling pathway. It may be a new promising treatment for erectile dysfunction and cardiovascular disease.